Item analysis to identify quality multiple choice questions/items in an assessment in Pharmacology of II MBBS students in Guntur Medical College of Andhra Pradesh, India - Suryadevara, Vijaya K.; Bano, Zaheda (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In medical education, multiple choice questions/Items are the more frequently used assessment tools to assess the knowledge abilities and skills of medical students, for being their objectivity, wide coverage in less time. However only the Quality Items gives a valid and reliable assessment. The quality of an Item is determined by difficulty index (DIF I), Discrimination Index (DI) and Distractor efficiency (DE). Aim of the study was to know the quality of Items in pharmacology by Item analysis and to develop a MCQs bank with quality Items. Methods: The present study was conducted on 150 II MBBS students of Guntur Medical College, AP, India. A class test containing 50 Items with 150 distractors from topic chemotherapy was conducted. Item with the correct choice/response was awarded with one mark and with the wrong choice zero marks, no negative marks. Each test Item was analysed with DIF I, DI and DE and the results were tabulated and tested statistically, with unpaired "t" test. Results: Mean DIF I, DI, DE values with standard deviations in the present study are 44.72+17.63%, 0.30+0.12%, 84.48+24.65 respectively. DIF I of 32 (64%) items was good to excellent range (31%-60%) 9 (18%) Items were easy (>61%) and 9(18%) Items were difficult (>30%). DI of 10 (20%) Items was good (0.15 to 0.24.) 29 (58%) Items were excellent with DI > 0.25 and 11 (22%) Items were poor with DI <0.15. Among 150 distractors, 127 (85%) were functional distractors (FDs) and 23 (15%) were non-functional distractors (NFDs). DE of 33 (66%) items with nil NFDs was 100%, for 12 (24%) Items with one NFD, was 66.6%, for 4 (8%) items with 2 NFDs was 33.3% and for 1 (2%) Item with 3NFDs DE was 0%. When unpaired "t" test was applied to the means of "difficult" and "easy" Items, 96.22+11.33% SD, 51.44+29.31% SD respectively, the p-value obtained was 0.00058, which was highly significant. Conclusions: The study showed that Item analysis is a valid tool to identify quality Items, which assess, the students’ knowledge abilities and discriminate different levels of performance abilities of students effectively.